Acute Chagas disease outbreaks in Colombia in 2019 (2024)
This study seeks to address the critical knowledge gap surrounding the acute phase of Chagas disease in Colombia, with a specific focus on cases reported in 2019. The acute phase of Chagas disease is a pivotal period for intervention, yet it remains poorly understood, particularly in regions where oral transmission is presumed to be a significant factor. By analyzing these recent cases, our research aims to provide a deeper understanding of the dynamics of Chagas disease during its acute phase in Colombia in 2019. This understanding is essential not only for improving disease management and treatment strategies but also for enhancing public health responses to this neglected tropical disease. In particular, our study highlights the importance of identifying and addressing the unique challenges posed by oral transmission routes, which have been increasingly recognized within Colombia’s Chagas disease landscape.